Reading the travel paintings of Cheng Haw Chien / Ngan Chew Pei - Ngan , Chew Pei (2018)
In Malaysia, academic research on Chinese ink brush painting is relatively uncommon and it is significantly rare to see a research on Chinese ink brush painting artist who possesses the three perfections—poem, calligraphy and painting—like Cheng Haw Chien. There has been a decline of artists in practicing the three arts of poetry, calligraphy and painting in the modern China due to their social system. In Malaysia, access to relevant resources on the three arts no doubt not comparable to the China. However, Cheng has successfully acquired the skills of producing the three arts through years of practice and persistent. Traditional Chinese ink brush painting has such a long history and that it is never easy to breakaway from what is so stagnant in term of its style and its techniques, and to be able to create something fresh and unique. This research intended to examine the new techniques and the style Cheng Haw Chien has showcased in his travel paintings as well as to interpret the poetry inscribed in his travel paintings so to allow readers or viewers to appreciate his artworks. These travel paintings capture Cheng’s travel experiences like a journal—a record of subjective experiences, reflections, and with profusion of literati tradition. The new techniques and style Cheng has developed is based from his strong understanding of the traditional ink brush techniques and with years of practices and experimenting on ink, colour and different types of paper. Visual analysis of Cheng’s travel paintings is performed by references to the literati painting theory and Lingnan painting theory. Interpretation of poetry inscribed and its meaning in relation to the travel paintings are perform based on the approach by Jonathan Chaves. It is this poetic inscription—capturing one’s subjective experiences—that has shaped Cheng’s travelling experiences and register his experience as a traveler. Through this analysis of Cheng Haw Chien’s travel painting, we can see that Cheng is able to capture and to present to the viewer his collective travelling experiences and his life as an artist, in both visual and verbal images, allowing viewers to appreciate his travel ink brush paintings in a whole new experience.